2013
DOI: 10.1038/pr.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein subfractions display proatherogenic properties in overweight and obese children

Abstract: Background:In adults, obesity-driven inflammation can lead to increased cardiovascular disease (CVD). However, information regarding childhood obesity and its inflammatory sequelae is less well defined. Serum amyloid-A (SAA) is an inflammatory molecule that rapidly associates with highdensity lipoproteins (HDLs) and renders them dysfunctional. Therefore, SAA may be a useful biomarker to identify increased CVD potential in overweight and obese children. Methods: Young Hearts 2000 is a cross-sectional cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…This mechanism might also explain the observed association between impaired HDL function and hypertension, which is strongly linked to oxidative stress [32]. In line with other studies demonstrating a negative effect of obesity on HDL function [33], we also detected a correlation between body mass index and antioxidant HDL function in premature AMI patients. The deleterious impact of smoking on HDL function has been previously shown and might be caused by oxidative modifications of HDL-associated proteins as well as a shift in particle size distribution towards smaller HDL particles [34,35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This mechanism might also explain the observed association between impaired HDL function and hypertension, which is strongly linked to oxidative stress [32]. In line with other studies demonstrating a negative effect of obesity on HDL function [33], we also detected a correlation between body mass index and antioxidant HDL function in premature AMI patients. The deleterious impact of smoking on HDL function has been previously shown and might be caused by oxidative modifications of HDL-associated proteins as well as a shift in particle size distribution towards smaller HDL particles [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…Generally, oxidative stress is regarded as crucial player in the development of dysfunctional HDL [30,31]. In line with other studies demonstrating a negative effect of obesity on HDL function [33], we also detected a correlation between body mass index and antioxidant HDL function in premature AMI patients. In line with other studies demonstrating a negative effect of obesity on HDL function [33], we also detected a correlation between body mass index and antioxidant HDL function in premature AMI patients.…”
Section: Discussionsupporting
confidence: 91%
“…Pietiläinen et al (2009) investigated HDL subfractions in young twin and found in abdominal overweight children decreased HDL2b and increased HDL3c subfractions independent of genetic influences. A marker for cardiovascular disease, serum amyloid-A was found to be positively correlated with small HDL subfractions in overweight children McEneny et al (2013).…”
Section: Introductionmentioning
confidence: 91%
“…ApoA-I in HDL has been identified as being responsible for reverse cholesterol transport and reverse atherosclerosis, and paraoxonase 1 in HDL has been found to have anti-oxidant properties [9]. In addition, studies have indicated that elevated amounts of serum amyloid A (SAA) in HDL render it pro-atherogenic [10], [11]. It has also been demonstrated that overexpression of apoA-II in HDL fractions advanced atherosclerosis even though the plasma levels of HDL-C were elevated [12].…”
Section: Introductionmentioning
confidence: 99%